Pendidikan Buddhis Di Era Milenial - Wati Tjakra (Sekolah Tinggi Agama Buddha Nalanda, 2020)
The Millennial Era is characterized by very high student dependence on social media and information technology. However, the dependence is not accompanied by the ability of students to sort information. This situation has the potential to endanger students. Buddhist education has the responsibility to free humanity from suffering. In the current context it means that students are intelligent and have character. To answer the needs in the millennial era, Buddhist education needs to make various improvements. This research focuses on Buddhist values that can be developed in the millennial era, as well as educational practices that bring progress.